2015
DOI: 10.1038/ncomms7478
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-catalysed reductive hydrogen atom transfer reactions

Abstract: Generally, transition metal catalysts are essential for the reductive hydrogen atom transfer reaction, which is also known as the transfer hydrogenation reaction or the borrowinghydrogen reaction. It has been reported that graphene can be an active catalyst in ethylene and nitrobenzene reductions, but no report has described carbon-based materials as catalysts for alcohol amination via the borrowing-hydrogen reaction mechanism. Here we show the results from the preparation, characterization and catalytic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 73 publications
2
66
0
1
Order By: Relevance
“…Hydrogen released from H-donor compounds could be reacted with hydrogen acceptors on catalytic active sites. Catalytic reduction of a molecule using hydrogen atom transferred from donor molecule is called transfer hydrogenation [27][28][29][30] . Transfer hydrogenation occurs at less severe operating condition compared to hydrogenation using explosive hydrogen [31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen released from H-donor compounds could be reacted with hydrogen acceptors on catalytic active sites. Catalytic reduction of a molecule using hydrogen atom transferred from donor molecule is called transfer hydrogenation [27][28][29][30] . Transfer hydrogenation occurs at less severe operating condition compared to hydrogenation using explosive hydrogen [31,32] .…”
Section: Introductionmentioning
confidence: 99%
“…[3] Therefore,development of metal-free catalysts is quite desirable. [4] Recently,c arbon materials with or without dopant have shown promising abilities in many organic reactions as one kind of metal-free heterogeneous catalysts,i ncluding Friedel-Crafts alkylation reactions, [5] reductive hydrogen atom transfer reactions, [6] and oxidation of alcohols, [7] amines, [8] and arenes. [9] Tw or ecent outstanding studies demonstrated that it is also feasible to catalyze oxidation of C À Hb onds with carbocatalysts.W ang et al reported boron and fluorine co-doped mesoporous carbon nitride (B,F-doped C 3 N 4 )asametal-free catalyst for selective oxidation of cyclohexane to cyclohexanone with H 2 O 2 as oxidant.…”
mentioning
confidence: 99%
“…Especially, incorporating graphitic-type nitrogen in carbocatalysts is pivotal for the CÀ H bond activation. [22] All these characteristics together make SDC-A an excellent metalfree catalyst for the oxidation of aromatic hydrocarbons. In addition, the sulfur dopants also play a role in modulating electronic structure of the carbon atoms.…”
Section: Resultsmentioning
confidence: 99%